Elaboración de un texto complementario, sobre la fauna del cantón Piñas para el cuarto año de educación general básica de la escuela Gonzalo Abad Grijalva del mismo cantón, aser aplicado desde el periodo lectivo 2013-2014 - Castillo Román, Liliana Claribel (2012)
It is precisely in this direction that the present proposal for intervention in the school curriculum of the children of fourth year of E.G.B. Of the schools of the canton Piñas, since it is sought to incorporate in its study pensum a textbook on the fauna of the canton, to be used as a pedagogical resource that facilitates the approach of teachers and students to the natural physical environment so that Learning is meaningful.